2005
DOI: 10.1002/cphc.200500115
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Dependence in the Methyl Vinyl Ketone+OH and Methacrolein+OH Oxidation Reactions: An Electronic Structure Study

Abstract: High-level electronic structure calculations were carried out for the study of the reaction pathways in the OH-initiated oxidations of methyl vinyl ketone (MVK) and methacrolein (MACR). For the two conformers of MVK (called synperiplanar and antiperiplanar), the addition channels of OH to the terminal and central carbon atom of the double bond dominate the overall rate constant, whereas the abstraction of the methyl hydrogen atoms has no significant kinetic role. In the case of MACR, only the antiperiplanar co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 117 publications
(136 reference statements)
2
8
0
Order By: Relevance
“…The optimized geometries of the two conformers have the C s symmetry as shown in Figure 1. The energy of ap conformer is lower than that of the sp conformer by 3.5 kcal mol −1 at the HL level of theory, which is in consistent with the theoretical results performed by Ochando-Pardo et al, who obtained the ap:sp ratio of 99.6:0.4, 8 and experimental results (97.5:2.5 and 100:0 at room temperature) also showed that the ap conformer of MACR has significant weight in its reactivity. 47 So only the ap conformer was taken into account for the mechanism and kinetics study of the Cl + MACR reaction, just like researchers did with the OH + MACR reaction.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The optimized geometries of the two conformers have the C s symmetry as shown in Figure 1. The energy of ap conformer is lower than that of the sp conformer by 3.5 kcal mol −1 at the HL level of theory, which is in consistent with the theoretical results performed by Ochando-Pardo et al, who obtained the ap:sp ratio of 99.6:0.4, 8 and experimental results (97.5:2.5 and 100:0 at room temperature) also showed that the ap conformer of MACR has significant weight in its reactivity. 47 So only the ap conformer was taken into account for the mechanism and kinetics study of the Cl + MACR reaction, just like researchers did with the OH + MACR reaction.…”
Section: Resultssupporting
confidence: 93%
“…47 So only the ap conformer was taken into account for the mechanism and kinetics study of the Cl + MACR reaction, just like researchers did with the OH + MACR reaction. 8,9 From the geometric structure of MACR shown in Figure 1, we can see that the Cl atom may react with MACR by the following possible paths: (1) addition, the Cl atom adds to the CC or the CO double bonds; (2) hydrogen atom abstraction, the Cl atom abstracts the aldehyde-H, the methyl-H, or the methylene-H atoms; (3) group abstraction, the Cl atom abstracts the −CH 3 or the −HCO group. In order to acquire the comprehensive reaction mechanism on which the kinetics calculation is based, we tried to calculate all of the above possible paths.…”
Section: Resultsmentioning
confidence: 99%
“…See ref. [20] for a complete electronic structure discussion of the whole potential-energy surface. MVK + OH system: As can be observed in Figure 1, two conformers of the MVK molecule were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…In this reaction only the ap conformer was taken into account because the population of the sp conformer is negligible at all the temperatures studied, in good agreement with experimental results. [20,[53][54][55] Determination of the location of the terminal addition transition-state structure of MACR, TSadd-t-ap2, is again awkward because the C À O distance between the fragments was found to be too long with MPW1K (3.2 ) and too short with MP2 (2.1 ). The same strategy as used for the TSadd-t-ap1 species of MVK was applied, the single point CCSD(T)/cc-pVTZ(Q)//MP2/6-31 + GA C H T U N G T R E N N U N G (d,p) energy barrier height finally being lowered 1.5 kcal mol…”
mentioning
confidence: 98%
See 1 more Smart Citation